2022
DOI: 10.3390/ijms23179633
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Magneto-Responsive Hydrogels from Dually Cross-Linked Polysaccharides: Synthesis, Tuning and Evaluation of Rheological Properties

Abstract: Smart hydrogels based on natural polymers present an opportunity to fabricate responsive scaffolds that provide an immediate and reversible reaction to a given stimulus. Modulation of mechanical characteristics is especially interesting in myocyte cultivation, and can be achieved by magnetically controlled stiffening. Here, hyaluronan hydrogels with carbonyl iron particles as a magnetic filler are prepared in a low-toxicity process. Desired mechanical behaviour is achieved using a combination of two cross-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Recently, smart hydrogels with stimulus-responsive functions have attracted considerable attention. Briefly, stimulus-responsive hydrogels can respond to internal physiological signals (i.e., temperature [ 28 , 29 ], pH [ 30 , 31 ], redox [ 32 , 33 ], glucose [ 34 , 35 ], or enzymes [ 36 , 37 ]), external stimuli (i.e., temperature [ 38 , 39 ], magnetic field [ 40 , 41 ], pressure [ 42 , 43 ], reactive oxygen species (ROS) [ 44 , 45 ], light [ 46 , 47 ] and electric field [ 48 , 49 ]) or a combination of the above, which can reversibly or irreversibly change the physical properties or chemical structure ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, smart hydrogels with stimulus-responsive functions have attracted considerable attention. Briefly, stimulus-responsive hydrogels can respond to internal physiological signals (i.e., temperature [ 28 , 29 ], pH [ 30 , 31 ], redox [ 32 , 33 ], glucose [ 34 , 35 ], or enzymes [ 36 , 37 ]), external stimuli (i.e., temperature [ 38 , 39 ], magnetic field [ 40 , 41 ], pressure [ 42 , 43 ], reactive oxygen species (ROS) [ 44 , 45 ], light [ 46 , 47 ] and electric field [ 48 , 49 ]) or a combination of the above, which can reversibly or irreversibly change the physical properties or chemical structure ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 In comparison, our HA hydrogels exhibited relatively low compressive moduli within a narrow range of 4.5-42.2 Pa. Others have found that a higher degree of modification for HA-ADH led to stiffer hydrogels, which was similar to what we observed for the 40 kDa hydrogels. 35 Ultimately, our method of fabricating hydrazone-crosslinked HA hydrogels yielded hydrogels with a wide range of physicochemical properties, including large ranges in hydrogel gelation time and mass change, with the capacity to swell, degrade, or maintain a relatively constant mass over 28 days depending on the molecular weight and concentrations of HA-ADH and HA-Ox used (Table 2).…”
Section: Hydrogel Mass Change Over Timementioning
confidence: 99%
“…[30][31][32] We formed HA hydrogels using dynamic covalent hydrazone crosslinks as this approach can yield a wide range of physicochemical properties, making them an attractive hydrogel platform for numerous regenerative medicine applications. [33][34][35][36][37][38][39][40] The properties of hydrazone-crosslinked HA hydrogels can be easily tuned by adjusting the ratios of the two dynamic covalent crosslinking polymers: oxidized HA (HA-Ox) and HA adipic acid dihydrazide (HA-ADH). Thus, we narrowed our input parameters to HA molecular weight, HA-Ox concentration, and HA-ADH concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This type of crosslinking can be controlled by light intensity and the irradiation time [63]. In addition, some tissue adhesives are crosslinked through a combination of multiple crosslinking strategies, such as the combination of ionic and covalent crosslinking [63], Schiff base and coordination crosslinking [15], and Schiff-base crosslinking and ionic crosslinking [64]. A multiply crosslinked tissue adhesive can show the advantages of each crosslinking type, and due to an increase in crosslinking density, the resultant tissue adhesive usually exhibits a better cohesive strength than singly crosslinked adhesives [15,64].…”
Section: Chitosanmentioning
confidence: 99%